The El Niño Southern Oscillation and the salinity of land and water in the United States - Nicola Limodio; Filippo De Marco; Ilaria Dal Barco (PLoS ONE, 2025)
The El Niño–Southern Oscillation (ENSO) is a periodic climate phenomenon with important consequences for weather and socioeconomic variables worldwide. This paper investigates the effect of El Niño on the concentration of salts in soils and fresh water. Our analysis shows effects that are statistically significant and large in magnitude. In particular, in response to El Niño events, soil salinity increases by 21% in the northern region of the United States, where average temperatures are positively affected, while it decreases by 29% on average in the southern tiers of the country, where temperatures decline. Similarly, fresh water salinity increases by 9% in warmer counties, while it is 53% lower in cooler counties.